Information technology and its impact on strategic performance in Yemeni telecommunications companies - Isam Ali Ahmed Al-Hamli; Senan Ghaleb Al-Marhdi (Problems and Perspectives in Management)
Information technology is critical to improve and raise the level of strategic performance of organizations. This study aimed to investigate the impact of information technology and information technology dimensions (hardware, software, databases, communication networks, and personnel skills) on the strategic performance of Yemeni telecommunications companies and assess the overall level of information technologies and strategic performance of respective companies. The study adopted a descriptive-analytical approach and used a questionnaire for data collection. The sample of the study comprised 560 employees out of the total population of 2,238 employees in chosen Yemeni companies. The selected employees included CEOs, deputy executive managers, department managers, section heads, supervisors, and specialists due to the relevance of their roles to information technology and strategic performance. Accordingly, 479 questionnaires were successfully retrieved and analyzed. The findings showed that information technology positively impacts strategic performance (R2 = 0.385; p < 0.05), indicating that information technology plays a significant role in enhancing strategic performance. The dimensions (hardware, databases, and personnel skills) have a statistically significant effect on strategic performance (β = 0.212, 0.205, 0.340; p < 0.05), while software and communication networks showed no statistically significant effect (β = 0.043, 0.033; p > 0.05). Additionally, the findings revealed a high level of information technology and strategic performance in Yemeni companies. These findings indicate that Yemeni telecommunications companies place significant emphasis on information technology and strategic performance.